Performance of the forward calorimeters forheavy-ion experiments at FAIR, NICA, and CERN SPS - Mikhaylov V. S. Vasily Sergeevich; Guber F. F. Fedor Fridrikhovich; Ivashkin A. P. Alexander Pavlovich; Kugler A. Andrey; Kushpil S. A. Svetlana Aleksandrovna; Kushpil V. Vasily; Svoboda O. Ondrey; Tlusty P. Pavel; Ladygin V. P. Vladimir Pertovich; Seddiki S. Selim; Selyuzhenkov I. V. Ilya Vladimirovich (2015, 2015)
Title screen